Unusual metastasis of left colon cancer: considerations on two cases - Gubitosi, A.; Moccia, G.; Malinconico, F. A.; Gilio et al., F. (Acta Biomedica Atenei Parmensis, 2009)
Usually, left colon cancer metastasis concerns liver, abdominal lymph nodes and lungs. Other localizations are quite rare occurrences. In spite of this, some uncommon metastasis sites are reported in literature, such as: peritoneum, ovaries, uterus, kidney testis, bones, thyroid, oral cavity and central nervous system. We report two cases of unusual localizations of left colon cancer metastasis localization, one into the retroperitoneal space and the other at the left axillary lynphnodes and between liver and pancreas. In the first reported case the diffusion pathway may have been the lymphatic mesocolic vessels, partially left in place from the previous surgery. In the second case the alleged metastatic lane may have been through the periumbilical lymph nodes to the parasternal lymph nodes and then to the internal mammary ones, finally reaching the axillary limph nodes.